GOVERNMENT REPOSITIONING IN ADDRESSING THE LEGAL VACUUM OF GLOBAL CITY PROJECT IN THE SPECIAL REGION OF JAKARTA AFTER THE CHANGE OF REGIONAL LEADERSHIP - Agnes Fitryantica; Lita Tyesta Addy Listya Wardhani; Ratna Herawati (Awang Long Law Review, 2026)
Global City project in the Special Region of Jakarta aims to position Jakarta as a central hub of global economic governance and connectivity, particularly through the service, technology, and innovation sectors. Jakarta is increasingly demonstrating its potential as a global city in Southeast Asia due to its strong economy, rapid infrastructure development, and implementation of the smart city concept. However, major challenges arise during leadership transitions. Many innovative projects are halted or redirected due to the absence of legal provisions requiring subsequent regional heads to continue previously initiated programs. This reflects a legal vacuum, especially due to the lack of long-term policy transition norms at the regional level. As a result, global city development policies are overly dependent on the political vision and mission of incumbent leaders. This research employs a normative and empirical juridical approach by analyzing relevant laws and regulations. The findings show that several major projects—such as Jakarta Smart City, Transit-Oriented Development (TOD), and urban village revitalization—have been delayed or altered due to the absence of binding rules ensuring continuity after a change in leadership. To address this issue, a repositioning of the government’s role is necessary. The central government must act as a guarantor of project continuity through national policies and strong legal frameworks. At the regional level, local regulations (Perda) must include clauses mandating policy continuity, cross-term reporting obligations, and stronger regulations concerning legacy projects within the framework of the Regional Government Law. These measures are essential to ensure the sustainable implementation of Jakarta’s global city vision, undisturbed by the five-year political cycle.